The Use of Commissive Speech Acts and Its Politeness Implication: A Case of Banten Gubernatorial Candidate Debate - Nabilah Fairus Al-Bantany (Passage, 2013)
This study entitled “The Use of Commissive Speech Acts and its Politeness Implication: A Case of Banten Gubernatorial Candidates Debate” examines the use of commissive speech acts in the Banten gubernatorial candidate debate and the realization of politeness in the use of the speech acts. This study is largely qualitative, supported by some descriptive quantification. Data were collected by downloading the debate from relevant websites. The data analysis was based on Searle’s (1979) classification of speech acts and Brown and Levinson’s (1987) theory of politeness. It is found that commissive speech acts were mostly realized through guarantee (53.7%), followed by promise (38.9%), and refusal (7.4%). It is also found that in terms politeness, all the candidates appear to behave in relatively the same way. This seems to result from the weightiness which is not largely different and the candidates’ consideration that the panelists and other candidates are only media to speak to a party that has the ultimate power, i.e. the people of Banten.Keywords: Speech Acts, Commissive Speech Acts, Politeness